The Influence of Current Ratio and Debt to Equity Ratio on Company Value (Tobin's Q) at PT Kalbe Farma, Tbk from 2012 to 2022 - Yuli Yanna Putri (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2023)
This study aims to test and determine the effect of the Current Ratio and Debt To Equity Ratio on Firm Value (Tobin's Q) at PT Kalbe Farma Tbk for the 2012-2022 period. In this study, researchers used secondary data by collecting financial report data through the Indonesia Stock Exchange (IDX) Website, namely www.idx.co.id and quantitative methods to determine the effect of the independent variables on the dependent variable and formulate hypotheses to be tested using the Eviews application. 2012. The results of this study indicate that partially (t test) the Current Ratio has no effect on firm value because the significance value is 0,1247>0,05 and the t value is -1,715037<2,36462 and the Return On Equity Ratio has no effect on firm value because the significance value is 0,4748>0,05 and the t-value is0,742981<2,36462. And simultaneously (F test), Current Ratio and Return On Equity Ratio affect firm value.